Data for tracking SDGs: challenges in capturing neonatal data from hospitals in Kenya - Hagel, C; Paton, C; Mbevi, G; English, M; Clinical Information Network (CIN) information systems interest group (BMJ Publishing Group, 2020)
Background Target 3.2 of the United Nations Sustainable Development Goals (SDGs) is to reduce neonatal mortality. In low-income and middle-income countries (LMICs), the District Health Information Software, V.2 (DHIS2) is widely used to help improve indicator data reporting. There are few reports on its use for collecting neonatal hospital data that are of increasing importance as births within facilities increase. To address this gap, we investigated implementation experiences of DHIS2 in LMICs and mapped the information flow relevant for neonatal data reporting in Kenyan hospitals.